2005
DOI: 10.1292/jvms.67.291
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gap Junctional Intercellular Communication (GJIC) through p38 and ERK1/2 Pathway in the Differentiation of Rat Neuronal Stem Cells

Abstract: ABSTRACT. Gap junctional intercellular communications (GJIC) contributes to neural function in development and differentiation of CNS. In this study, we have investigated the expression of GJIC during the differentiation of neuronal stem cells and 12-Ø-tetradecanoylphorbol-13-acetate (TPA)-induced neuronal stem cell-derived cells from rat brain. During neuronal stem cell differentiation, expressions of Cx43 and 32 were increased for the duration of 72 hr, however the effect were decreased on the 7d. In the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…Introducing gap junction proteins (Cxs) into cell lines has been shown to enhance bystander cell death [41]. In addition, gap junction blocker carbenoxolone could reduce OGD-induced neuronal death in hippocampal slice cultures [42]. Consistent with these reports, in this study, we found the quantitative inverse relationship between Cx32 expression and hippocampal neuron viability.…”
Section: Discussionsupporting
confidence: 89%
“…Introducing gap junction proteins (Cxs) into cell lines has been shown to enhance bystander cell death [41]. In addition, gap junction blocker carbenoxolone could reduce OGD-induced neuronal death in hippocampal slice cultures [42]. Consistent with these reports, in this study, we found the quantitative inverse relationship between Cx32 expression and hippocampal neuron viability.…”
Section: Discussionsupporting
confidence: 89%
“…Lastly, rat brain derived NS/PC express Cx43 and Cx45 and communicate through GJIC, which is essential for their survival and proliferation . In these cells, Cx32 and Cx43 are upregulated during differentiation (Yang et al, 2005). Similar data were observed in mouse fetal NS/PC, where the closure of gap junctions decreases cell proliferation and reduces cell survival Duval et al, 2002).…”
Section: Somatic Stem Cellssupporting
confidence: 57%
“…Neural stem cells isolated from the rat developing brain express Cx43 and Cx45 and are capable of forming GJIC, where GJIC is essential for survival and proliferation in these cells [14]. Moreover, Cx43 and Cx32 levels were observed to increase temporarily during differentiation in these cells [131]. Future studies on human neural stem cells will help address whether this role of gap junctions is conserved among species.…”
Section: Neural Stem Cellsmentioning
confidence: 99%